HALAL CUISINE PREFERENCES IN URBAN AREAS WITH MUSLIM MINORITY: A CASE RESEARCH OF MANADO - Samad, Telsy Fratama Dewi; Sugeng, Anggoro; Ayub, Talha; Taufani, Taufani (AKADEMIKA: Jurnal Pemikiran Islam, 2022)
The phenomenon of halal cuisine is gaining prominence not only within Muslim communities but also in non-Muslim region. Therefore, this research aimed to explain the phenomenon of halal cuisine in Muslim minority region of Manado, North Sulawesi, Indonesia. Using a qualitative research design with a case research method, interviews were conducted with five Muslim merchants to gather pertinent information. The results showed the presence of Muslim merchants selling halal cuisine in Manado, despite it being Muslim minority area. Merchants expressed confidence in the potential development of halal cuisine in the region. Additionally, the use of halal signs (logo) by Muslim merchants served to assure customers of halal status of their products. It was also observed that both Muslim and non-Muslim customers patronized the merchants, showing a broad appeal for halal cuisine. In conclusion, despite Manado being recognized as a Muslim minority region, Muslim merchants played a significant role in promoting their halal cuisine within the region.